2015
DOI: 10.1186/s12992-015-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Pharmaceutical Pricing Transparency Matter? Examining Brazil’s Public Procurement System

Abstract: BackgroundWe review procurement and pricing transparency practices for pharmaceutical products. We specifically focus on Brazil and examine its approach to increasing pricing transparency, with the aim of determining the level of effectiveness in lower prices using a tool (Banco de Preços em Saúde, BPS) that only reveals purchase prices as compared to other tools (in other countries) that establish a greater degree of price transparency.MethodsA general report of Preços em Saúde (BPS) and Sistema Integrado de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 12 publications
(12 reference statements)
1
42
0
2
Order By: Relevance
“…Hence, price reductions may be attributable to greater purchasing leverage, in addition to improved transparency. However, inconclusive findings on cost-savings were reported in a 2015 analysis of Preços em Saúde (BPS), Brazil's drug procurement system, which assessed changes in the prices of drugs whose acquisition prices were made publicly available on the Internet [61]. The study assessed purchases made by all federally funded hospitals in two socioeconomically distinct Brazilian states, Pariba and São Paulo, over a five-year period.…”
Section: Text Box 2 (Brazil Case Study)mentioning
confidence: 99%
“…Hence, price reductions may be attributable to greater purchasing leverage, in addition to improved transparency. However, inconclusive findings on cost-savings were reported in a 2015 analysis of Preços em Saúde (BPS), Brazil's drug procurement system, which assessed changes in the prices of drugs whose acquisition prices were made publicly available on the Internet [61]. The study assessed purchases made by all federally funded hospitals in two socioeconomically distinct Brazilian states, Pariba and São Paulo, over a five-year period.…”
Section: Text Box 2 (Brazil Case Study)mentioning
confidence: 99%
“…It also provides technical and quality requirements for the various types of procurement contracts. However, the process that is used to determine a 'reasonable' price is unclear (Kohler, Mitsakakis, Saadat, Byng, & Martinez, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, improvement in availability of medicines has not been assessed. Experiences with PAHO’s Revolving Fund [60, 61], and centralized procurement mechanisms used in Brazil [62], Argentina, Uruguay, and in Chile [63, 64] have shown that by consolidating product requirements and increasing purchase volumes, purchasers can benefit from economies of scale leading to lower prices and increasing procurement efficiency [61, 65]. Thus, the extended use of pooled procurement has indeed the potential to promote efficiency and reduce variations in medicines prices within the Mexican public sector.…”
Section: Discussionmentioning
confidence: 99%
“…However, its potential is currently limited as only few institutions use it. Brazil, Colombia, Argentina and Peru have also implemented medicines’ pricing information systems to monitor medicines prices, with the ultimate goal to increase transparency and improve access [64, 74, 81, 82]. These systems could serve as examples for Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation